Seismic Fragility Analysis of an Isolated Continuous Girder Bridge Using the Response Surface Method with Random Factors. Issue 12 (December 2015) - Long, X.H.; Fan, J.; Yang, B.B.; Chen, B.L.
To improve the efficiency of seismic fragility analysis, this paper analyzes the seismic fragility of isolated continuous girder bridges by adopting the response surface method with random factors. A three-dimensional finite element model is established for a typical RC isolated continuous girder bridge in western China using the finite element analysis software OpenSees. Next, test samples are determined according to experimental design theory by simultaneously accounting for the uncertainty of the structure itself and the earthquake ground motion. The response surface models of the scenario's structural capability can be obtained in terms of the numerical calculation results, after which structural parameter sensitivity analysis is conducted. On this basis, a seismic fragility curve for the major components and structural system can be obtained by the Latin Hypercube method. The analysis shows that concrete's compressive strength is the dominant factor affecting structural capacity in the parameter sensitivity analysis. Use of isolation bearing greatly reduces the possibility of pier damage by contrasting the seismic fragility curve. Briefly, the application of this method not only decreases the workload immensely, providing a new idea for seismic fragility analysis, but also has significant, practical value for the design and optimization of similar isolated bridges.